2020
DOI: 10.1111/1365-2745.13455
|View full text |Cite
|
Sign up to set email alerts
|

Gene flow effects on populations inhabiting marginal areas: Origin matters

Abstract: The evolutionary potential of populations inhabiting marginal areas has been extensively debated and directly affects their conservation value. Gene flow is one of the main factors influencing selection, adaptive potential and thus, local adaptation processes in marginal areas. The effects of differential gene flow provenance are still not well understood, since studies on gene flow between marginal populations have been underrepresented in the literature. This kind of gene flow can be especially beneficial be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 93 publications
0
23
0
2
Order By: Relevance
“…The experimental gene flow design was not reciprocal as it was focused on studying the effects of assisted gene flow on the marginal populations occurring at the low elevation distribution edge. Thus, the recipients of gene flow treatment were always the marginal populations as in previous study assessing similar questions (see Morente-López et al, 2020a).…”
Section: Gene Flow Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental gene flow design was not reciprocal as it was focused on studying the effects of assisted gene flow on the marginal populations occurring at the low elevation distribution edge. Thus, the recipients of gene flow treatment were always the marginal populations as in previous study assessing similar questions (see Morente-López et al, 2020a).…”
Section: Gene Flow Treatmentsmentioning
confidence: 99%
“…However, gene flow effects on the adaptive potential of recipient populations are closely related to the specific environmental conditions of the original and recipient populations. In this sense, Morente-López et al (2020a) showed that gene flow between marginal populations that share similar environmental conditions increase genetic diversity and provide adaptive alleles. Other studies point to a reduction of fitness in marginal populations due to the incorporation of maladapted alleles from optimal populations (Dawson et al, 2010;Fedorka et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A pesar de los niveles sustanciales de flujo genético encontrados entre poblaciones, todavía existen algunos niveles de aislamiento que generan una estructura genética y, en consecuencia, puede existir diferenciación fenotípica asociada a procesos neutrales como la deriva genética, los cuellos de botella o efectos fundadores. En uno de los pocos estudios realizados para testar el efecto diferencial del flujo genético con respecto a su origen, encontramos que la supervivencia de las plántulas resultantes del flujo genético entre poblaciones marginales fue mayor que la de plántulas resultantes del flujo genético de poblaciones óptimas a poblaciones marginales (Morente-López et al 2020b). Ambas son etapas vitales cruciales para la especie ya que su mayor cuello de botella demográfico se encuentra en la fase de reclutamiento (Giménez-Benavides et al 2008;Giménez-Benavides et al 2011b).…”
Section: El Flujo Genético Como Fuerza Que Da Forma a Las Respuestas Adaptativasunclassified
“…En este contexto, los resultados de los experimentos de siembra cruzada realizados con S. ciliata mostraron una mayor tasa de supervivencia de las plántulas procedentes de poblaciones marginales, tanto cuando eran sembradas en áreas óptimas como en áreas marginales. Esto indica una mayor capacidad de adaptación de las poblaciones marginales que de las poblaciones óptimas a las condiciones ambientales existentes en las fases de germinación y establecimiento (Morente-López et al 2020b). Este hallazgo asegura y refuerza el potencial adaptativo presente en poblaciones marginales expuesto en puntos anteriores basado en la diversidad genética presente y la capacidad de las poblaciones de divergir fenotípicamente en respuesta a unas presiones selectivas dadas (García-Fernández et al 2012a;Lara-Romero et al 2016a;Morente-López et al 2018).…”
Section: Potencial Adaptativo Y Valor Evolutivo De Las Poblaciones Marginalesunclassified